Ulipristal Acetate Interferes With Actin Remodeling Induced by 17β-Estradiol and Progesterone in Human Endometrial Stromal Cells - Shortrede, Jorge E.; Montt-Guevara, Maria M.; Pennacchio, Gisela; Finiguerra, Michele; Giannini, Andrea; Genazzani, Alessandro D.; Simoncini, Tommaso (Frontiers in Endocrinology, 2018)
Ulipristal acetate (UPA) is a selective progesterone receptor modulator (SPRM) used for emergency contraception and for the medical management of symptomatic uterine fibroids (UF). Treatment with UPA turns in amenorrhea and UF volume reduction. Treatment with UPA is associated with the frequent development of benign, transitory endometrial changes known as SPRM-associated endometrial changes (PAECs). Why PAECs develop and their biological or cellular basis is unknown. Sex steroids, including estrogen and progesterone, are established modulators of the actin cytoskeleton in various cells, including endometrial cells. This explains several morphological and functional changes in endometrial cells. We thus hypothesized that UPA may alter the appearance of the endometrium by interfering with the actions of 17β-estradiol (E2) or progesterone (P4) on actin dynamics. We isolated and cultured human endometrial stromal cells (ESC) from endometrial biopsies from healthy fertile women. Treatment with E2 or P4 stimulated visible actin rearrangements with actin remodeling towards the membrane. Activation through phosphorylation of the actin regulatory proteins, Moesin and focal adhesion kinase (FAK), hacked actin remodeling induced by E2 and P4. Membrane re-localization of Paxillin and Vinculin were also induced by E2 and P4, showing the formation of focal adhesion complexes. All these E2 and P4 actions were inhibited by co-treatment with UPA, which was otherwise inactive if given alone. The cytoskeletal changes induced by E2 and P4 turned into increased motility of ESC, and UPA again blocked the actions E2 and P4. In conclusion, we find that UPA interferes with the cytoskeletal actions of E2 and P4 in ESC. This finding helps understanding the mode of actions of SPRMs in the endometrium and may be relevant for other potential clinical applications of UPA.